Rediscovery of nycticebus coucang insularis Robinson, 1917 (Primates: Lorisidae) at Tioman Island and its mitochondrial genetic assessment - Ryan, Jeffrine J. Rovie; Millawati Gani,; Han, Ming Gan; Gilmoore G. Bolongon,; Tan, Cheng Cheng; Norazlinda Razak,; Norsyamimi Rosli,; Mohd Azizol Aziz,; Kalip MatKasim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Slow lorises (Nycticebus) consist of eight species native to Southeast Asia while three species are recognised in Malaysia - N. coucang, N. menagensis and N. kayan. This study reports on the rediscovery of the subspecies N. coucang insularis Robinson, 1917 in Tioman Island and the genetic assessment of its mitochondrial DNA variation. Morphological measurements conform the specimen as the putative N. coucang but with distinct colour and markings. Two mitochondrial DNA segments (cytochrome b and control region) were produced from the subspecies representing their first registered sequences in GenBank. Genetically, the subspecies showed 99% of nucleotide similarity to N. coucang species type for both the DNA segments and constitute its own unique haplotype. Phylogenetic trees constructed using three methods (neighbour joining, maximum likelihood and Bayesian inference) showed two major groups within Nycticebus; the basal group was formed by N. pygmaeus while the second group consisted of the remaining Nycticebus species. The phylogenetic position of the subspecies, however, remains unresolved due to the observed mixing between N. coucang and N. bengalensis. Several reasons could lead to this condition including the lack of well documented voucher specimens and the short DNA fragments used. In addition, the possibility of hybridisation event between N. coucang and N. bengalensis could not be excluded as a possible explanation since both species occur sympatrically at the Isthmus of Kra region until the Thailand-Malaysia border. The rediscovery of this subspecies displays the unique faunal diversity that justifies the importance of Tioman Island as a protected area.